2014
DOI: 10.2903/j.efsa.2014.3907
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Chloramphenicol in food and feed

Abstract: Chloramphenicol is an antibiotic not authorised for use in food-producing animals in the European Union (EU). However, being produced by soil bacteria, it may occur in plants. The European Commission asked EFSA for a scientific opinion on the risks to human and animal health related to the presence of chloramphenicol in food and feed and whether a reference point for action (RPA) of 0.3 µg/kg is adequate to protect public and animal health. Data on occurrence of chloramphenicol in food extracted from the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 392 publications
(534 reference statements)
0
28
0
Order By: Relevance
“…This is very interesting because CAP metabolism in primary turkey hepatocyte cultures has never been studied. The in vivo studies with poultry indicate that CAP metabolism differs from that of rats in the formation and excretion of glucuronide and reduction of the nitro group [2,42]. We found that the concentrations of the nontoxic metabolite, CAP-G, in turkey hepatocyte cultures were lower than those in equivalent rat hepatocyte cultures.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This is very interesting because CAP metabolism in primary turkey hepatocyte cultures has never been studied. The in vivo studies with poultry indicate that CAP metabolism differs from that of rats in the formation and excretion of glucuronide and reduction of the nitro group [2,42]. We found that the concentrations of the nontoxic metabolite, CAP-G, in turkey hepatocyte cultures were lower than those in equivalent rat hepatocyte cultures.…”
Section: Discussionmentioning
confidence: 64%
“…Chloramphenicol (CAP) is a broad-spectrum antibiotic used in medicine. Its use in food-producing animals is banned due to the potentially carcinogenic action of CAP residue and the development of non-dose-related aplastic anemia in humans [1,2]. However, this antibiotic is used illegally in veterinary practice, and its residues are found in food from animals (milk (0.005-0.5 µg/L), honey (0.1-75 µg/kg), eggs (0.9 µg/kg), fish and shrimp (0.01-242 µg/kg), meat (0.004-0.01 µg/kg), turkey breasts (1-8.7 µg/kg), and chicken breasts (range, 0.4-1.2 µg/kg)) [3][4][5] and the environment (sediments (0.196 mg/kg), surface water (112 ng/kg)) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations